Physical Activity Levels in Physical Education Lessons at Singapore Primary School - Jamaluddin, Nur Syahida Binte; Kawabata, Masato (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2021)
Physical education (PE) lessons are the appropriate occasions to promote physical activity for children. Although the moderate-to-vigorous physical activity (MVPA) levels during PE lessons were investigated in several countries, MVPA levels during PE lessons were never reported at Singapore primary schools. Therefore, the present study aimed to investigate physical activity intensity levels during PE lessons at a Singapore primary school. A total of 93 students (40 girls) voluntary participated in the study: 28 in Grade 1, 39 in Grade 4, and 26 in Grade 6. They were asked to wear an accelerometer on their non-dominant hand in two PE lessons to measure physical activity levels objectively. They also completed questionnaires on their experiences during the PE lessons. The average of the MVPA levels time (%) in the scheduled lesson time across the three grades was 46.98 ± 5.25%, but the average of the MVPA levels time (%) in the actual lesson time was 69.74 ± 7.31%. These results indicated that it would be possible to achieve the recommended MVPA time in PE lessons. The findings of this study would be useful for PE teachers to reflect whether their PE lessons are efficient to promote primary school student’s physical activity levels.